2019
DOI: 10.3390/dj7040108
|View full text |Cite
|
Sign up to set email alerts
|

Is the Use of Antimicrobial Photodynamic Therapy or Systemic Antibiotics More Effective in Improving Periodontal Health When Used in Conjunction with Localised Non-Surgical Periodontal Therapy? A Systematic Review

Abstract: Periodontal disease can be treated in several ways. This paper reviewed whether antimicrobial photodynamic therapy (aPDT) in addition to scaling and root planing (SRP) produces improved clinical results over systemic antibiotics (ABs) in conjunction with SRP in adults with periodontitis. Studies were searched using the following electronic databases: MEDLINE, the Cochrane Database of Systematic Reviews, and the Web of Science Core Collection up to and including November 2018. Four randomized controlled trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Smoking was considered an important risk factor that affects the speed of disease progression, and we decided not to exclude the study with smokers [19], since it makes a direct comparison between the two groups, not mixing smoking and non-smoking patients, and the limited amount of papers present in the literature. Thus, our findings for the comparison of SRP+aPDT with the SRP+AMX+ MTZ for the non-surgical treatment of periodontitis are in agreement with the other two [31,32] similar reviews previously published. Although of the new studies added, of narrowing the comparison with only a combination of antibiotics and pointing out new possibilities of bias in the included studies, we cannot conclude that any of the studied therapies present better or worse results for any of the analyzed clinical parameters.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Smoking was considered an important risk factor that affects the speed of disease progression, and we decided not to exclude the study with smokers [19], since it makes a direct comparison between the two groups, not mixing smoking and non-smoking patients, and the limited amount of papers present in the literature. Thus, our findings for the comparison of SRP+aPDT with the SRP+AMX+ MTZ for the non-surgical treatment of periodontitis are in agreement with the other two [31,32] similar reviews previously published. Although of the new studies added, of narrowing the comparison with only a combination of antibiotics and pointing out new possibilities of bias in the included studies, we cannot conclude that any of the studied therapies present better or worse results for any of the analyzed clinical parameters.…”
Section: Discussionsupporting
confidence: 92%
“…Periodontitis is one of the most common inflammatory diseases in humans [28], and AMX+MTZ is the combination of antibiotics most used as an adjunct treatment in non-surgical periodontal treatment [29,30]. Two reviews similar to this one were published previously, in 2017 [31] and 2019 [32], although they did not include recent studies published in 2018 [19], and approved for publication in 2020, with an online version in 2019 [18], in addition to not focusing on the combination of antibiotics studied in this review, giving a possible bias to the results that could be attributed to the type of antibiotic used instead of analyzing the effectiveness of antibiotic treatment as a better or worse adjunctive therapy than aPDT for periodontitis. Teugheus, et al [13] in a recent systematic review showed that the association of AMX+MTZ in the adjunctive treatment of periodontitis had the best clinical periodontal improvements when compared to amoxicillin and metronidazole used alone, azithromycin, clarithromycin and moxifloxacin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2019 systematic review analyzed whether SRP plus antimicrobial photodynamic therapy exerted an improved clinical outcome in comparison to SRP plus systemic antibiotics in periodontal disease. Although there were significant improvements for both treatment modalities, the inter-group discrepancy was not statistically significant in a consistent manner, and further studies are necessary in order to state a definite conclusion [58].…”
Section: Antibiotics Vs Antimicrobial Photodynamic Therapy (Apdt)mentioning
confidence: 81%
“…Regarding periodontitis, if the use of antibiotics as an adjunct needs justification, Maan et al [ 123 ] in their systematic review concluded that better clinical outcomes are observed, supported by another systematic review and meta-analysis by Zhao et al [ 124 ], who compared systemic antibiotics and PDT as adjuncts in periodontitis and peri-implantitis. Another review [ 125 ] contradicts such observations by stating that both systemic antibiotics and PDT as adjuncts in periodontitis (it did not include peri-implantitis) were not convincing in obtaining clinical improvements in probing depths, clinical attachment levels and bleeding on probing. The systematic review by Øen et al in 2021 [ 126 ] opined that adjunctive systemic antibiotics cannot be considered as standard treatment in peri-implantitis.…”
Section: Pdt For Peri-implant Diseasesmentioning
confidence: 99%